Do Green Finance and Islamic Financial Literacy Drive SDG Achievement? A Panel Study of Indonesian Islamic Banks: english - Lukman Hakim; Dewi Oktayani; Kiki Candri; Muhammad Elsa Tomisa; Susilawati Susilawati (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study investigates the role of green finance in supporting the achievement of the Sustainable Development Goals (SDGs) within Indonesian Islamic banking, with Islamic financial literacy incorporated as a moderating variable. Using panel data from eight Islamic commercial banks over the 2020–2024 period, the study applies a fixed-effects regression model to analyze the relationships among variables. The findings indicate that green finance has a positive and statistically significant effect on SDG achievement, highlighting the importance of sustainability-oriented financing in promoting environmental and social outcomes. Islamic financial literacy is also found to have a direct positive impact on SDG performance, suggesting that higher levels of public understanding of Islamic financial principles enhance the effectiveness of sustainable finance initiatives. Furthermore, the interaction between green finance and Islamic financial literacy is significant, implying that financial literacy strengthens the influence of green finance on sustainable development outcomes. In contrast, conventional financial indicators, such as Return on Equity (ROE) and leverage, do not show significant effects on SDG achievement. These results emphasize that value-based and knowledge-driven factors play a more critical role than traditional profitability measures in advancing sustainability within Islamic banking. This study contributes to the literature by integrating green finance and financial literacy perspectives, while also providing practical implications for policymakers and financial institutions to enhance sustainability strategies through financial education and green financing initiatives.